2014
DOI: 10.1136/bmjopen-2014-005346
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for coronary artery disease in an urban Indian population

Abstract: ObjectiveThe objective of this study was to assess the prevalence of risk factors for coronary artery disease (CAD) in government employees across India.MethodsThe study population consisted of government employees in different parts of India ({n=10 642 men and n=1966 women; age 20–60 years}) and comprised various ethnic groups living in different environmental conditions. Recruitment was carried out in 20 cities across 14 states, and in one union territory. All selected individuals were subjected to a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 15 publications
9
61
4
1
Order By: Relevance
“…The prevalence of CAD is not only very high in Indian subcontinent but also in migrant Asian Indians. Migrant Indians in USA have 4 times prevalence rate than native white Americans [5][6][7]. Coronary artery disease occurs prematurely and is more severe in the Indian population as compared to any other ethnic group in the world [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CAD is not only very high in Indian subcontinent but also in migrant Asian Indians. Migrant Indians in USA have 4 times prevalence rate than native white Americans [5][6][7]. Coronary artery disease occurs prematurely and is more severe in the Indian population as compared to any other ethnic group in the world [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Low prevalence was reported by, Parikh S. et al 7 in Ahmedabad city which was 37% in males and 36% in females. Garg A. et al 8 reporting 33.7% males and 31.5% females were hypertensive while Sekhri T. et al 9 reported that 22.4% of males and 13.4% of females were hypertensive.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension in the present study is higher than this research. A multicentric study across different regions of India by Sekhri et al (17) reported prevalence for overweight/obesity of 46.1% among males and 55.3% among females. The difference between males and females was statistically significant however no such difference was observed in this study.…”
Section: Discussionmentioning
confidence: 99%